ANALISIS KESALAHAN SISWA BERDASARKAN TIPE NEWMAN DALAM MENYELESAIKAN SOAL EKSPONEN PADA SISWA KELAS X SMA AT-TAUBAH TIRTAMULYA - Jihan Putri Nur'aini; Dadang Rahman Munandar (IKIP Siliwangi, 2021)
The purpose of this study was to find out how big the level of student error when solving mathematical problems on exponential material based on the type of Newman error in class X MIPA 1 SMA At-Taubah Tirtamulya which consisted of several types of errors including (1) errors due to lack of accuracy or carelessness, (2) errors in process skills, (3) errors in understanding questions, (4) errors in notation, and (5) errors in concept. There were 20 students during the research and then 5 subjects were selected for analysis and interviews. This type of research is descriptive qualitative. This study uses data collection techniques in the form of description tests and interviews. This study uses data analysis techniques, namely reducing data, presenting data, and drawing conclusions. The result of the study found that students errors when working on exponential material problems with the types of errors due to lack of accuracy or carelessness, errors in process skills, errors in understanding questions, and errors in using notation were classified as very low, while the types of errors in concept were classified as moderate. The type of student error that the researchers found the least in this study was notational error, while errors in concepts were the most common errors found in this study.